2015
DOI: 10.1002/uog.14863
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of small-for-gestational-age neonates: screening by biophysical and biochemical markers at 30-34 weeks

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 30 publications
6
54
0
1
Order By: Relevance
“…The authors reported an 89% detection rate for SGA newborns with a 10% false positive rate, combining maternal characteristics, obstetric history, and fetal biometric measurements. Bakalis et al [36] reported a 65% detection rate of SGA (<5 th centile) neonates with delivery at ≥37 weeks when the EFW assessed at 30–34 weeks was combined with maternal factors, uterine artery PI, mean arterial pressure, and serum placental growth factor. The results described herein for single biometry at ≤32 weeks in a mostly African-American population are in very good agreement with these previous findings as we report about a 50% sensitivity for both SGA (<5 th centile) and LGA (>95 th centile) prediction (FPR = 10%).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported an 89% detection rate for SGA newborns with a 10% false positive rate, combining maternal characteristics, obstetric history, and fetal biometric measurements. Bakalis et al [36] reported a 65% detection rate of SGA (<5 th centile) neonates with delivery at ≥37 weeks when the EFW assessed at 30–34 weeks was combined with maternal factors, uterine artery PI, mean arterial pressure, and serum placental growth factor. The results described herein for single biometry at ≤32 weeks in a mostly African-American population are in very good agreement with these previous findings as we report about a 50% sensitivity for both SGA (<5 th centile) and LGA (>95 th centile) prediction (FPR = 10%).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, earlier GA at sampling may explain the lack of association, as angiogenic imbalance is likely to be progressive. More recently, a large prospective study conducted at 30-34 weeks' gestation concluded that a combined screening, including maternal factors, EFW, UtA-PI, MAP and serum PlGF without inclusion of sFlt-1 can predict at 10% false-positive rate, 57% of SGA neonates delivering at ≥37 weeks with a birth weight <10th percentile [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Impaired placentation, reflected in increased pulsatility index (PI) in the uterine arteries (UtAs), reduced serum placental growth factor (PlGF) and increased soluble fms‐like tyrosine kinase‐1 (sFlt‐1) is associated with subsequent development of pre‐eclampsia (PE) and delivery of a small‐for‐gestational‐age (SGA) neonate. Another marker of development of PE is increased mean arterial pressure (MAP). Impaired placentation is also associated with fetal hypoxemia and consequent redistribution in the fetal circulation, reflected in reduced fetal middle cerebral artery (MCA) PI and increased UA‐PI.…”
Section: Introductionmentioning
confidence: 99%